The Effect of Developing Process Standards and Content Standard Development on Improving The Performance of Chemical Teachers of Negeri High Schools in Bandung District - Iis Suryani; Dr. Ujang Cepi Barlian, M.Si. (Green Publisher Indonesia, 2021)
This study examines the problem of developing process standards and content standards which are important variables in improving teacher performance. Teacher performance is increasingly important to improve in line with the increasingly complex demands of teachers as professionals. The purpose of this study was to describe and analyze the influence and comparison of the development of process standards and content standards on improving teacher performance which focused on the main problems, namely: (1) the magnitude of the influence of developing process standards on teacher performance, (2) the magnitude of the influence of developing content standards on performance. teachers, and (3) the magnitude of the influence and comparison of the development of process standards and content standards simultaneously on improving the performance of state high school chemistry teachers in Bandung Regency. In this study, the Embedded Concurent model of the Mix Methods approach was used. Data were analyzed using descriptive analysis techniques and inferential analysis techniques. The results of the analysis show that the development of process standards and content standards together contributes positively and significantly to improving teacher performance, which is stated based on the positive correlation coefficient and determination coefficient values ​​with an effect of 76%, meaning that the effect is good, this proves that the better the development of standard processes and the development of content standards are carried out, the better the increase in teacher performance. Meanwhile, the remaining 24% is influenced by other variables